Taxonomic review of genus Danielithosia Dubatolov & Kishida (Lepidoptera, Erebidae, Arctiinae) from northern Vietnam, with one new species - Bayarsaikhan, Ulziijargal; Dubatolov, Vladimir V.; Heppner, John B.; Bae, Yang-Seop (Zootaxa, 2017)
Four species of the genus Danielithosia Dubatolov & Kishida, 2012, are reported from northern Vietnam: Danielithosia immaculata (Butler, 1880), Danielithosia hoenei Dubatolov, 2013, Danielithosia zolotuhini Dubatolov, 2012, and Danielithosia baviensis n. sp. Illustrations of adults and genitalia are presented, with species descriptions and notes.